POTENSI DAN TANTANGAN MANAJEMEN PEMASARAN SYARIAH DALAM INDUSTRI MARKETPLACE HALAL DI INDONESIA - Putri, Mutiara Eka; Zaelani, Abdul Qodir; Fasa, Muhammad Iqbal; Ronaldo, Reza (ANALISIS, 2024)
The advancement of information technology has given rise to various types of online transactions, one of which is marketplace trading. At present, Indonesia is the country with the largest Muslim population in the world, reaching 86.9% of the total population, and they are also active in online shopping. Although awareness and public interest in halal products is increasing, an understanding of the urgency of transactions in accordance with sharia principles is still needed. The purpose of this research is to identify market opportunities as well as existing challenges in order to formulate strategies for developing sharia marketing management in halal marketplaces to be more optimal and in accordance with sharia principles. The research method used in this study is a literature study method. The results show that halal marketplaces in Indonesia have the potential for a large market and are an innovation from previously existing marketplaces. However, in addition to this potential, there are a number of challenges in developing a halal marketplace, including the lack of public understanding of the sharia economy, lack of involvement in the sharia financial system, and the still limited use of the halal marketplace platform by MSMEs focusing on halal products. It is hoped that this potential and challenges can serve as a guide in formulating and developing policies in this field.